2021
DOI: 10.1186/s13054-021-03595-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of early extubation followed by noninvasive ventilation versus standard extubation on the duration of invasive mechanical ventilation in hypoxemic non-hypercapnic patients: a systematic review and individual patient data meta-analysis of randomized controlled trials

Abstract: Background Usefulness of noninvasive ventilation (NIV) in weaning patients with non-hypercapnic hypoxemic acute respiratory failure (hARF) is unclear. The study aims to assess in patients with non-hypercapnic hARF, the efficacy of NIV after early extubation, compared to standard weaning. Methods In this individual patient data meta-analysis, we searched EMBASE, Medline and Cochrane Central Register of Controlled Trials to identify potentially eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…95 b. NIPPV is associated with lower rates of intubation, reintubation, VAP, and mortality compared to conventional oxygen therapy in patients with acute hypercapnic or hypoxemic respiratory failure. [96][97][98][99][100] Use caution when considering NIPPV to manage patients with impaired consciousness, acute lung injury, acute respiratory distress syndrome, severe hypoxemia, severe acidemia, or when continuing NIPPV for patients whose dyspnea or gas exchange fails to rapidly respond to NIPPV. Helmet ventilation may be associated with better outcomes than facemask ventilation.…”
Section: Essential Practices For Preventing Vap And/or Vaes In Adult ...mentioning
confidence: 99%
“…95 b. NIPPV is associated with lower rates of intubation, reintubation, VAP, and mortality compared to conventional oxygen therapy in patients with acute hypercapnic or hypoxemic respiratory failure. [96][97][98][99][100] Use caution when considering NIPPV to manage patients with impaired consciousness, acute lung injury, acute respiratory distress syndrome, severe hypoxemia, severe acidemia, or when continuing NIPPV for patients whose dyspnea or gas exchange fails to rapidly respond to NIPPV. Helmet ventilation may be associated with better outcomes than facemask ventilation.…”
Section: Essential Practices For Preventing Vap And/or Vaes In Adult ...mentioning
confidence: 99%
“…14 This prospective single-center pilot study assessed feasibility and safety of early extubation. 15,16 followed by sequential use of NIV and HFNT in consecutive blunt chest trauma patients admitted to ICU between January 2nd 2017 and December 31st 2019. The study was approved by the local Ethics Committee and registered.…”
Section: To the Editormentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in Table 1 . The correct Table is given hereafter.…”
Section: Correction To: Vaschetto Crit Care (2021) 25:189 101186/s13054-021-03595-5mentioning
confidence: 99%
“…All the changes that were requested are implemented in this correction and the original article [ 1 ] has been corrected.…”
Section: Correction To: Vaschetto Crit Care (2021) 25:189 101186/s13054-021-03595-5mentioning
confidence: 99%